Oxytocin Massage Increase Milk Production During Breastfeeding - Siti Farida; Etik Sulistyorini; Radettya Bella Retnaning Pangestu (Proceeding of International Conference on Science, Health, And Technology, 2021)
Breast milk is the main food for babies at the age of 6 months of life. Breast milk, which is produced naturally by the body, contains nutrients that are essential for the baby's growth and development. However, in practice there are still many problems in breastfeeding. Mothers do not give breast milk to their babies, especially in the first days of life because milk production is not smooth. Therefore, to prevent the failure of early breastfeeding, efforts are needed to speed up breastfeeding, one of which is oxytocin massage. Oxytocin massage is a massage performed on breastfeeding mothers on the back, to help increase the production of the hormone oxytocin and also prolactin which helps the body in the process of expressing breast milk. Oxytocin massage can be used in postpartum mothers. This type of research is quantitative research, quasi-experimental. Quasi experimental research design with pre and post test without control. The effectiveness of the treatment was assessed by comparing the post-test scores with the pre-test scores. Based on the results of the Wilcoxon Test, the Sig (2-tailed) results showed a value of 0,005 (p value <α 0.05) so that the results obtained that H0 was rejected and Ha was accepted, which means that there was a significant difference before and after massage oxytocin in increasing breast milk production. Oxytocin massage can effectively increase milk production with a mean result of -2,840.